Thermal stability and gaseous exhaust products of bovine leather for firefighter boots - Flinčec Grgac, Sandra (Array, 2019)
This paper aims to investigate fire resistance properties of two samples of fireproof bovine leather; both with smooth and perforated brushed surfaces. Apart from flammability and flame spreading, an important property is heat resistance and the development of gaseous products that occur during heat degradation. For the purpose of characterizing those properties, cowhide leather samples were exposed to thermogravimetric analysis (TGA) of monitoring gaseous degradation products (TG-IR) during decomposition. Considering the results of fire resistance, it can be concluded that tested samples of smooth bovine leather show satisfactory stability to the influence of flame and heat, while perforated brushed fireproof leather with artificial surface was partially pouched and gathered in the area of direct contact with flame. Both samples show similar behavior during TGA, but differences have been observed in the analysis of gaseous degradation products.